Sintering effects and hydrothermal ageing behaviour of Yttria-stabilised zirconia with MnO2 doping / Ting Chen Hunt - Ting , Chen Hunt (2018)
YSZ ceramics has outstanding mechanical properties and has been used for many engineering applications. However, a major drawback of this ceramic is the undesirable ageing-induced tetragonal to monoclinic phase transformation resulting in properties deterioration when exposed to steam environment. In most cases for commercial YSZ powders, high sintering temperature or/and long holding time are required via the common pressureless sintering approach which leads to grain growth exceeding the critical size that triggered low temperature degradation consequently lead to structural failure. One possible approach to suppress the excessive grain growth of YSZ is conducting low temperature sintering by adding small amount of MnO2 as sintering aid. The present work investigate the influence of low temperature sintering, focusing on varying sintering holding times on the mechanical properties, microstructure and low temperature degradation behavior of undoped and MnO2 (0.5 & 1.0 wt%) doped YSZ ceramics were investigated. Green samples were sintered at temperatures ranging from 1100 to 1250 ºC at varying holding times from 12 min to 480 min. The sintered bodies were characterized in terms of bulk density, fracture toughness, Vickers hardness, phase stability and microstructure evolution. Hydrothermal ageing tests up to 120 hr were conducted at 180 ºC with pressure 10 bar in an autoclave. The amount of monoclinic ZrO2 on the aged surface was measured by X-ray diffraction (XRD). Another group of undoped YSZ samples were pressureless sintered at higher temperatures (1200 to 1500 ºC) with standard heating rate 10 ºC/min and holding time, 120 min were prepared for comparison purpose. Densification and mechanical properties of YSZ ceramics were improved even at low sintering temperature when doped with MnO2 additive. The results indicated the relative density of above 95 %, Vickers hardness of 14 GPa and fracture toughness of 5 MPam1/2 were obtained when sintered at low sintering temperature of 1150 ºC, holding time 480 min or 1250 ºC, 12 min respectively for 1.0 wt% MnO2-doped YSZ ceramics. Grain growth at low sintering temperature was marginal and the average grain size of all samples ranged between 0.14 to 0.28 μm. The results indicated that the grain growth kinetics was influenced mainly by the sintering temperature and not by the sintering holding time. The low temperature degradation (LTD) experiment conducted in superheated steam for 120 hr indicated that all the undoped YSZ ceramics via standard heating profile and temperature < 1300 ºC showed no the monoclinic phase which attributed to the lower grain size and homogeneous distribution of yttria in the tetragonal grains. However, small traces of monoclinic phase was formed in MnO2-doped YSZ ceramics even at low sintering temperature, 1200 & 1250 ºC and the rate of transformation was increased with higher amount of dopant and longer sintering holding time beyond 120 min which could be attributed destabilising of tetragonal grain as the result of redistribution of yttria in the grain. Ageing mechanism was subsequently proposed to account for the LTD behaviour of the YSZ ceramics.